IoT-based Real-Time Monitoring System to Optimize Capacitor Bank Performance on Waste Chopping Machines in Cikawao Village, Bandung - Adiprabowo, Tjahjo; Ramdani, Dani; Andriana, Andriana; Turesna, Ganjar; Zulkarnain, Zulkarnain; Sukmana, Raden; Fauziah, Rahma Nur; Hendrawan, Lara Dwi Cinta; Direja, Aura Anbiya; Sambas, Tresna Intan Maulani; Resnitiani, Della Agni; Dhanureksa, Prima (Internet of Things and Artificial Intelligence Journal, 2025)
The use of waste chopping machines in Cikawao Village, Bandung depends on the electricity that supplies the machine. To supply electrical energy to the chopping machine, bank capacitors are needed which function to stabilize electrical power. A capacitor bank is a set of capacitors installed in parallel. Specifically, the function of the capacitor bank is to improve the power factor, reduce useless reactive power, reduce power losses on the network, increase the available power capacity, and also stabilize the system voltage. In this article review, the hope is that the voltage can be monitored in real-time using the Internet of Things (IoT) and focus on voltage sensors and current sensors and controllers that work like relays when the voltage is over, it will automatically turn off. And voltage (V) and current (I) can be monitored in real-time on the available monitors. In the process of building this IoT, a protocol is needed, to control and monitor voltage and electric current can use a microcontroller that can connect to the internet, which means using a WiFi module and connecting it to the Internet server using the MQTT Protocol.